Nur al-Din al-Raniri’s selected commentaries on other religions in the 17th century Malay world - Abdul Jalil, Mohd. Noh; Alias, Majdan (Department of Islamic History And Civilization, Academy of Islamic Studies, University of Malaya, Kuala Lumpur, 2020)
This article analyzes selected commentaries of Nur al-Din al-Raniri (d. 1658) to the discourse on religions other than Islam in the Malay world. Such discourse was not common during the early period of Islam in the region. Malay Muslim scholars at that time were focusing more on other discipline of knowledge in Islam. Despite the scarcity of such discourses, it was not totally abandoned. This article employs textual analysis. It analyzes three works by al-Raniri on religious discourses focusing on religions other than Islam namely Tibyan fi Ma’rifat al-Adyan, Asrar al-Insan fi Ma’rifat al-Ruh wa al-Rahman and Bustan al-Salatin. Textual analysis on these texts are made to understand the priority he had at that time in making such discourses. Apart from textual analysis, this article also highlights al-Raniri’s strong connection with the Malay world despite not a Malay himself. Efforts made by al-Raniri in writing on religions other than Islam in his works proved that such discourse did exist during the early period of Islam in the Malay world. In fact, it was a continuation of similar discourse by other Muslim scholars world wide at that time.